Progress in Canadian Mechanical Engineering. Volume 3 2020
DOI: 10.32393/csme.2020.1257
|View full text |Cite
|
Sign up to set email alerts
|

Continuum Dislocations and Active Single-slip Assumption in MicroMechanical analysis of Matrix Dominated Composite Unit cell

Abstract: The key purpose of this paper is to propose a mono-slip dependent continuum dislocation method to MDCS (matrix dominated composite structure) analysis. The methodology focused on the dissipation energy theories using CDM (continuum dislocations method) integrated with the kinematics of small strain. The mathematical modeling of CDM comprises active mono-slip system formulations, thermodynamic dislocation analysis (TDA), energy dissipation analysis on the free form, and the progressions of dislocations. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, experimental investigations have indicated that dislocations in a strained crystal do not act in a fully random arrangement. Along with the above limitation, the distorted MDCS does not have a consistent dislocation density from one end to the other in the inner structure of the unit cell [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experimental investigations have indicated that dislocations in a strained crystal do not act in a fully random arrangement. Along with the above limitation, the distorted MDCS does not have a consistent dislocation density from one end to the other in the inner structure of the unit cell [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%